On the efficiency of piezoelectric energy harvester with exponentially tapered cantilever beam - Nguyen, Ngoc Linh (2020)
This paper theoretically examines the efficiency of exponentially tapered cantilever piezoelectric energy harvester which is subjected to base excitation. In anaysis models, the lumped parameters of composite beam such as natural frequency, equivalent stiffness and mass are defined from the continuous model firstly, then they are used in discrete model which is gorvened by electromechanically coupled governing equations. Based on the discrete model, a recently estimation of efficiency is applied to evaluate the transferred energy rate of exponentially tapered cantilever piezoelectric energy harvester with various shape.